The demise of islet allotransplantation in the United States: A call for an urgent regulatory update. Issue 4 (10th February 2021) - Witkowski, Piotr; Philipson, Louis H.; Kaufman, Dixon B.; Ratner, Lloyd E.; Abouljoud, Marwan S.; Bellin, Melena D.; Buse, John B.; Kandeel, Fouad; Stock, Peter G.; Mulligan, David C.; Markmann, James F.; Kozlowski, Tomasz; et al.
Abstract : Islet allotransplantation in the United States (US) is facing an imminent demise. Despite nearly three decades of progress in the field, an archaic regulatory framework has stymied US clinical practice. Current regulations do not reflect the state‐of‐the‐art in clinical or technical practices. In the US, islets are considered biologic drugs and "more than minimally manipulated" human cell and tissue products (HCT/Ps). In contrast, across the world, human islets are appropriately defined as "minimally manipulated tissue" and not regulated as a drug, which has led to islet allotransplantation (allo‐ITx) becoming a standard‐of‐care procedure for selected patients with type 1 diabetes mellitus. This regulatory distinction impedes patient access to islets for transplantation in the US. As a result only 11 patients underwent allo‐ITx in the US between 2016 and 2019, and all as investigational procedures in the settings of a clinical trials. Herein, we describe the current regulations pertaining to islet transplantation in the United States. We explore the progress which has been made in the field and demonstrate why the regulatory framework must be updated to both better reflect our current clinical practice and to deal with upcoming challenges. We propose specific updates to current regulations which are required for the renaissance of ethical, safe, effective, and affordable allo‐ITx in the United States. Abstract : This viewpoint delineates the progress made in the field of islet transplantation over the last three decades and proposes updates to the regulatory framework that currently governs islet allotransplantation in the United States to better reflect current clinical practice and recent state‐of‐the‐art advances.